Development of Indonesian Maritime Sovereignty Culture Through Indonesian Maritime Policy with Indonesian Maritime Defense Strategy - Labandi Labandi; Moch Haris (Universitas Lambung Mangkurat, 2023)
In the past, Indonesia wielded a significant influence over the Southeast Asia region and beyond, particularly through the Srivijaya Kingdom and later Majapahit's maritime prowess. Indonesia's natural affinity for maritime culture predates its very conception and is evident in the vast territorial waters surrounding almost all of its provinces. This unique geographical aspect makes Indonesia an archipelagic state with a maritime tradition. To support Indonesia's maritime defense, it is crucial to promote the prosperity of its maritime affairs. The country's national defense strategy takes into account its archipelagic nature. Maritime culture is a key aspect of the five pillars that drive Indonesia towards becoming a World Maritime Fulcrum. This policy point recognizes that a robust maritime culture is fundamental to the formation of Indonesia's maritime defense. Strong maritime culture begets a robust maritime defense, highlighting the interdependence of these two critical components. Keywords: maritime culture, maritime defense, maritime power, world maritime fulcrum